Friends rock - Burnell, Heather Ayris; Quintanilla, Hazel, 1982- (New York, NY : Acorn, Scholastic Inc., 2019)
Unicorn and Yeti are still a little new to the friendship-thing, but they are trying hard to work out how to share the things they like to do, for instance taking turns on a swing, or sharing a sparkly rock--or combining the peaches that Unicorn likes with Yeti's ice cream to make a special treat they can share together.
1.5.
K-3.
300L
Keywords: Unicorns -- Juvenile fiction; Yeti -- Juvenile fiction; Friendship -- Juvenile fiction; Sharing -- Juvenile fiction; Humorous stories; Unicorns -- Fiction; Yeti -- Fiction; Friendship -- Fiction; Sharing -- Fiction; Humorous fiction